Problems in testing digital protective relay for immunity to intentional destructive electromagnetic impacts. Continuation of the theme - Gurevich, V. (Електротехніка і електромеханіка, 2015)
The article is the continuation of the theme highlighted in the previous article with same title. The new article evaluates the results of digital protective relays (DPR) testing for immunity to the E1 component of High-altitude Electromagnetic Pulse (HEMP) and to Intentional Electromagnetic Interferences (IEMI) impacts, conducted by some independent American organizations; discusses the features of relay protection devices as well as clarifies and supplements the procedure for testing these devices. Due to methodology errors during the DPR tests conducted by mentioned organizations earlier, they cannot be considered as satisfactory and their results as meaningful. At the moment there are no reliable data on the level of DPR immunity to IDEI, which suggests that the test should be conducted further.